The Role of T-Cell Leukemia Translocation-Associated Gene Protein in Human Tumorigenesis and Osteoclastogenesis - Shigeru Kotake (Journal of Biomedicine and Biotechnology, 2012)
Synovial tissues of patients with rheumatoid arthritis (RA) include factors regulating bone resorption, such as receptor activator NF-κB ligand (RANKL), TNF-α, IL-6, IL-17, and IFN-γ. However, in addition to these cytokines, other factors expressed in synovial tissues may play a role in regulating bone resorption. In 2009, we demonstrated that novel peptides from T-cell leukemia translocation-associated gene (TCTA) protein expressed in synovial tissues from patients with RA inhibit human osteoclastogenesis, preventing cellular fusion via the interaction between TCTA protein and a putative counterpart molecule. Only a few studies on the role of TCTA protein have been reported. Genomic Southern blots demonstrated a reduced TCTA signal in three of four small cell lung cancer cell lines, suggesting the loss of one of the two copies of the gene. In the current paper, we reviewed the roles of TCTA protein in lung cancer cell lines and human osteoclastogenesis.